CONDUTAS QUE DETERMINAM O CRIME DE EXERCÍCIO ILEGAL DA MEDICINA - Poubel de Castro Júnior, Adilson; Silva Costa, Leandro; José de Castro Costa, Carlos (LINKSCIENCEPLACE, 2026)
The exercise of medicine, which is a priesthood, is a sacred activity for many, but although it is subject to such benefits, it presents certain requirements for its proper fulfillment. In the patriarchal order, some conduct that bears nobility in its achievements, among them medicine, can cause harm to an indeterminate number of people. An agent who appears to know medicine, but not who has never attended academic banks or those who, for various reasons, have not registered an appropriate registration with the competent organs, may lack the necessary prognoses and may result in worsening the health of those seeking cure. In the same vein, graduates in medical art who act in disparate behaviors of their specialties, with latent and natural malpractice in their actions, will bring hardening of anomalies instead of the relief given. For these reasons, criminal law, meets the social fact, prohibits such conduct, penalizing them, with provisos of states of emergency or need, in addition to the atipicidades in the conduct that subsumed to the one listed in the norm, but divorce from the deceit as the continuous care and immanent to the parents.